2016
DOI: 10.1021/acs.jpca.6b03770
|View full text |Cite
|
Sign up to set email alerts
|

Assigning the Cerium Oxidation State for CH2CeF2 and OCeF2 Based on Multireference Wave Function Analysis

Abstract: The geometric and electronic structure of the recently experimentally studied molecules ZCeF2 (Z = CH2, O) was investigated by density functional theory (DFT) and wave function-based ab initio methods. Special attention was paid to the Ce-Z metal-ligand bonding, especially to the nature of the interaction between the Ce 4f and the Z 2p orbitals and the possible multiconfigurational character arising from it, as well as to the assignment of an oxidation state of Ce reflecting the electronic structure. Complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16] This redox chemistry is relevant to both fundamental and applied research. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] For example, multi-configurational ground states have recently been revealed in several molecular and solid-state Ce(IV) materials. 25,[29][30][31][32][33][34][35][36][37] Moreover, X-ray absorption spectroscopy and density functional theory studies on tetravalent cerium have revealed considerable covalency and f orbital participation in Ce(IV)-L bonding.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10][11][12][13][14][15][16] This redox chemistry is relevant to both fundamental and applied research. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] For example, multi-configurational ground states have recently been revealed in several molecular and solid-state Ce(IV) materials. 25,[29][30][31][32][33][34][35][36][37] Moreover, X-ray absorption spectroscopy and density functional theory studies on tetravalent cerium have revealed considerable covalency and f orbital participation in Ce(IV)-L bonding.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] For example, multi-configurational ground states have recently been revealed in several molecular and solid-state Ce(IV) materials. 25,[29][30][31][32][33][34][35][36][37] Moreover, X-ray absorption spectroscopy and density functional theory studies on tetravalent cerium have revealed considerable covalency and f orbital participation in Ce(IV)-L bonding. [24][25][26][27][28][29]38 In addition, the Ce(IV/III) redox couple has proved instrumental for separation of cerium from mineral ores and in the mechanism of action of several ceria-supported catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Covalent contributions to the bonds of all these elements are dominantly based on the (n−1)d orbital overlap interactions. In period 6, the energy and radius of the 4f shell lends itself to additional covalent bond contribution in Ce(III) and in a few praseodymium compounds (Dolg and Moossen, 2015;Moossen and Dolg, 2016;Zhang et al, 2016;Hu et al, 2017;Smiles et al, 2020). Elsewise, the 4f level is too contracted, sitting inside the atomic core with outer (n−1)p 6 shell (Figure 8), but can store electrons thereby changing the oxidation state, the number of d-valence electrons and the ionic core radius (Dognon, 2014(Dognon, , 2017Liu et al, 2017;Pathak et al, 2017;Lu et al, 2019).…”
Section: The Heavy Early D-block Elements Including the F-blockmentioning
confidence: 99%